Effect of prognostic nutritional index on short-term survival after transcatheter aortic valve implantation - Cafer Panç; Emre Yılmaz; İsmail Gürbak; Fatih Uzun; Mehmet Ertürk (KARE Publishing, 2020)
Objective: Transcatheter aortic valve implantation (TAVI) is a good alternative to surgical aortic valve replacement (SAVR) in severe aortic stenosis patients who are at intermediate or high risk, or other cases that are considered unsuitable for SAVR. TAVI is most often performed on elderly patients, and although conventional risk scores include a number of comorbidities, they do not take into account functional decline specific to elderly patients. The prognostic nutritional index (PNI), which is a simple and effective parameter for both nutritional and inflammatory status, reflects functional decline in the elderly. The aim of this study was to determine the effect of the PNI on short-term survival after TAVI. Methods: The PNI values of 302 patients who underwent TAVI were analyzed. The study population was divided into 2 groups according to a PNI cut-off value: PNI >43.37 (n=213; 70%) and PNI <43.37 (n=89; 30%). Results: Patients with a lower PNI score had a significantly higher mortality rate in the initial 30-day period following the procedure than patients with a higher PNI score (3.3% vs. 31.5%; p<0.001). Major vascular complications and cardiac tamponade were significantly more frequent in the lower PNI group. The cut-off value of the PNI for 30-day survival was 43.37, with 94.3% specificity and 73.4% sensitivity and the negative predictive value of the PNI was 96.7%. The PNI score was found to be an independent risk factor for 30-day mortality after TAVI. Conclusion: A higher PNI score was associated with short-term survival and fewer post-TAVI complications.